DESAIN FONDASI TELAPAK DENGAN MENGGUNAKAN BETON STYROFOAM RINGAN PADA TANAH LEMPUNG BERPASIR - Irdhiani, Irdhiani; Ramadhani, Sriyati (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2014)
Recently, the price of construction material has gone up especially price of cement as the primary material for foundation construction. In the area which is consist of soft soil with higher water level, a higher foundation section area such as plate foundation or pile foundation is needed. It will be costly when pile foundation or plate foundation utilized in lightweight building. Therefore, lightweight concrete foundation might be useful as an alternative to reduce cement volume in concrete material which will reduce the cost of foundation construction. The research aims to determine the optimum percentage of lightweight Styrofoam concrete in plate foundation against bearing capacity, settlement, and uplift force in sandy clay.  Foundation were made of concrete mixed with Styrofoam with contents varied as 0%, 20%, 40%, 60% 80%  and 100%, then its pressure strength and volume weight at 28 days cure were tested. From physical properties tests such as sieve analysis and Atterberg limit test, the soil classified as CL or anorganic clay with low to medium plasticity, sandy clay with A(activity) of 0.87 which means it has illite clay mineral content in the soil with activity (A) medium.  Direct shear test shows that the soil have a friction angle (f) 24,25° and cohesion (c) 0,0197 kg/cm.  Concrete unit weight containing no Styrofoam is 2,222 gr/cm3. Average concrete unit weight will be reduced as 0,2726 gr/cm or 12% for each addition of 20% of Styrofoam. The percentage of concrete pressure strength reduction by addition of Styrofoam of 10%, 20%, 30%, and 40% compare to concrete pressure strength with no Styrofoam added are 24,470%, 44,453 %, 58,601 %, and 69,145 % respectively Reduction of  concrete pressure strength are due to Styrofoam particles that may act as air void, in which concrete with air void has lower pressure strength compare to concrete without air void. Kata Kunci : Plate Foundations, Lightweight Styrofoam Concrete, Sandy Clay